Present-day stress orientation in Thailand's basins - Tingay, Mark; Morley, C.; Hillis, R.; Meyer, J. (Pergamon-Elsevier Science Ltd., 2010)
The Cenozoic tectonic evolution of Thailand is widely considered to have been primarily controlled by forces generated at the eastern Himalayan syntaxis. This hypothesis is supported by earthquakes in northern Indochina and southern China, which reveal a fan-shaped present-day maximum horizontal stress (SHmax) pattern centered on the eastern Himalayan syntaxis. However, the distance to which forces generated by the Himalayan syntaxis influence the stress pattern in Indochina is not known. We analyzed caliper and image logs from 106 petroleum wells for borehole breakouts and drilling-induced fractures. A total of 558 breakouts and 45 drilling-induced fractures were interpreted in six basins, indicating that a north–south regional present-day SHmax exists in central and southern Thailand and the Gulf of Thailand. The N–S SHmax orientation suggests that forces generated at the Himalayan syntaxis are a major control on the stress pattern throughout Thailand, extending approximately 1000 km beyond the outer limit of syntaxis-associated seismicity.Despite the influence of the Himalayan syntaxis on the present-day stress field, the sedimentary basins of central, southern and offshore Thailand are characterized by structural styles that are somewhat inconsistent with those predicted to result from India–Eurasia collision. Furthermore, localized variations in SHmax orientation, and the predominance of structures associated with purely extensional rifting, indicate that other processes also influence the stress field in Thailand. We suggest that stresses generated by the Sumatran–Andaman subduction zone may also have resulted in significant deformation in offshore Thailand and that the stress pattern may also be perturbed at very local (several km) scales by mechanically weak faults.